1997
DOI: 10.1093/clinchem/43.9.1641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new immunoenzymometric assay for measuring soluble transferrin receptor to detect iron deficiency in anemic patients

Abstract: During the last few years the measurement of serum-soluble transferrin receptor (sTfR) has been introduced as a tool to detect iron deficiency and as an analyte to differentiate between anemia caused by iron deficiency (IDA) and that caused by chronic disease (ACD). Commercially available methods have emerged to make diagnostics by sTfR more readily accessible. We documented the analytical performance of a newly introduced IDeATM sTfR immunoenzymometric assay (IEMA) by Orion Diagnostica. We also evaluated its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 32 publications
1
25
0
3
Order By: Relevance
“…The number of transferrin receptors expressed on the cell surface reflects the iron requirements of a tissue (9, 23). Iron deprivation induces a prompt synthesis of the transferrin receptor (9). Increased blood sTfR values are usually observed in iron-depleted states, whereby the concentration of sTfR correlates inversely with the amount of iron available for erythropoiesis (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of transferrin receptors expressed on the cell surface reflects the iron requirements of a tissue (9, 23). Iron deprivation induces a prompt synthesis of the transferrin receptor (9). Increased blood sTfR values are usually observed in iron-depleted states, whereby the concentration of sTfR correlates inversely with the amount of iron available for erythropoiesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Serum transferrin receptor levels were determined by an immunoenzymometric method using IDeA 2 sTfR kits (Orion Diag-nostica, Orion Co., Finland). The sTfR test was performed as described previously (9). We diluted and reanalysed any sample that had a concentration higher than the highest calibrating standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory criteria for ID include a low MCV, a low concentration of serum ferritin and transferrin saturation (Mast et al, 1998). In recent years free erythrocyte protoporphyrin (FEP) and zinc protoporphyrin (ZPP), sTfR, sTfR/ferritin ratio and reticulocyte Hb content (CHr) have also been used to detect the onset of ID erythropoiesis (Hastka et al, 1996;Major et al, 1997;Suominen et al, 1997;Goodnough, Skikne & Brugnara, 2000;Ullrich et al, 2005;Angeles Vazquez Lopez et al, 2006).…”
Section: S U M M a R Ymentioning
confidence: 99%
“…It was shown that the sTfR-concentration depends on the erythropoietic activity as well as on iron metabolism. Elevated sTfR values were measured in patients suffering from hematological disorders with increased erythropoiesis like hemolytic anemia, thalassemia, spherocytosis, or polycythemia vera (8)(9)(10)(11)(12)(13)(14)(15)(16), but also in patients with ID (9,10,(17)(18)(19)(20)(21)(22)(23)(24)(25). In ID patients, the sTfR does not increase before IDE has developed.…”
mentioning
confidence: 99%